Psychological distress across the deployment cycle: comparing pre- and peri-pandemic trajectories - Antje H. Bühler; Gerd-Dieter Willmund (BMC Public Health)
Abstract Background To prevent military personnel from becoming vectors of SARS-CoV-2 transmission during the pandemic, soldiers throughout the world were required to quarantine before and after deployment. This study examined whether deployment-related quarantining affected trajectories of psychological distress for German military personnel throughout the deployment cycle. Pandemic-specific mental health studies were criticised for lacking a pre-pandemic reference point. This study aims to address this gap, thus providing stronger evidence as to whether deployment-related quarantining affected psychological distress. Method Pre-pandemic data were pooled with peri-pandemic data. The pre-pandemic sample consisted of 96 soldiers, and the sample from the pandemic group included 95 soldiers. Both groups completed the Brief Symptom Inventory (BSI)/Mini-Symptom Checklist (Mini-SCL) at three time points: two weeks before deployment, two weeks after deployment, and at a follow-up, three to six months post-deployment. The pandemic sample participated in both pre-deployment and post-deployment quarantines, completing the Mini-SCL five times. A two-way repeated-measures ANOVA assessed differences across deployment phases and time periods. Results The repeated measures ANOVA revealed significant main effects for the within-subjects factor "deployment phases" and the between-subjects factor "pre- versus peri-pandemic period," with a significant interaction between both factors. Follow-up analyses showed 1) differing pre- and peri-pandemic trajectories of psychological distress across the deployment cycle and 2) higher levels of psychological distress during the peri-pandemic period, except for the two-week post-deployment measurement, which coincided with the end of post-deployment quarantine. Conclusions While it is difficult to disentangle the specific impact of the pandemic versus deployment-related quarantine measures, the findings suggest that the pandemic itself had a more substantial impact on psychological distress than the quarantine measures. This study underscores the importance of selecting critical measurement time points, and utilising shorter, streamlined measures in future research.